Post-exercise hypotension in concurrent training: a systematic review - Diego De Mello; Thatiane Lopes Valentim Di Paschoale Ostolin (Universidade Federal de Santa Catarina, 2020)
Physical exercise is capable to reduce blood pressure (BP) acutely in a phenomenon described as post-exercise hypotension (PEH). However, the acute effect of concurrent training on PEH needs clarification. The present review aimed to verify and summarize the acute effect of concurrent training on PEH in normotensive and hypertensive subjects. The search was carried out in the databases PubMed, Scielo, and Lilacs, and resulted in 3806 articles. Only 14 studies met the eligibility criteria and were selected. According to included studies, concurrent training can promote PEH regardless of the order, volume, and intensity prescribed, being an effective strategy in the control of arterial hypertension. There is no consensus in the literature regarding the best prescription strategy, as well as the order of execution of the types of exercise.